Alcohol in minors - a harmless fad or a serious problem? - Świątek, Gabriela; Tkaczyk, Rafał; Sosnowska, Weronika; Tomkiewicz, Maria; Taracha, Kalina; Tomczyk, Jakub; Tomkiewicz, Maciej; Brzozowska, Aleksandra; Śwital, Magdalena; Tokarski, Michał (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Alcohol has been known for centuries. In recent years, awareness of the effects of its consumption has been growing and acceptance of the drink has been declining. Despite this, there is an increase in young alcohol consumption and a decrease in the age of alcohol initiation. In this work, the problem of alcohol consumption by minors will be reviewed based on the evaluation of hospitalizations in the Clinical Department of Toxicology and Cardiology of the Stefan Cardinal Wyszynski Regional Hospital in Lublin in 2022. The aim of the study is to draw attention to this important, although often downplayed, problem. Material and method: The study was retrospective in nature. It used an analysis of the records of 120 intoxications in people under the age of 18, from which a group of alcohol-poisoned people was distinguished, consisting of 37 cases. Results: Hospitalization of 7 patients aged 13 to 18 years was reported due to alcohol intoxication. Of these, 22 (59.5%) female and 15 (40.5%) male patients were singled out. Most were urban residents 29 (78.4%). Isolated alcohol intoxication was the cause of 18 hospitalizations(48.6%). The remaining cases were accompanied by drug intoxication 11 hospitalizations (29.7%) and drug intoxication 8 hospitalizations (21.6%). All analyzed intoxications were intentional, of which 9 (24.3%) were suicide attempts. In 14 cases (37.9%), patients were burdened with mental illness, the most common of which was depressive disorders. There were no deaths in the study group. Conclusions: Alcohol should be forbidden and unacceptable in the family and young people's environment. Parents and young people should be made aware of the harmful effects, psychological, social and health consequences of its consumption.